ANALISIS STABILITAS DINDING PENAHAN TANAH TERHADAP DRAWDOWN PADA LERENG SUNGAI AREA DAM BADENG KECAMATAN SONGGON, BANYUWANGI. - Holis Nurshinta; Paksitya Purnama Putra; Indra Nurtjahjaningtyas (FROPIL (Forum Profesional Teknik Sipil), 2021)
The Badeng River, which is located in Songgon District, Banyuwangi Regency, has a discharge that often overflows, causing damage to the retaining wall and erosion of the riverbank slopes of the Badeng Dam area. This is a problem for local residents because the use of water becomes less than optimal and can increase the risk of flooding in the downstream area of the river. To prevent landslides on the river bank, slope stability analysis is carried out using a gravity type retaining wall that can withstand overturning, shearing forces, and is safe against carrying capacity and pays attention to drawdown. The drawdown analysis was modeled for 20 hours at the initial condition of the river water level receding towards flooding and then returning to its original condition.. Modeling is done with Geoslope studio. The results of the gravity wall stability analysis against drawdown are declared safe. When the river water level is higher, the slope safety factor value will increase. Otherwise, when the river water level decreases, the slope safety factor value will decrease. This happens because it is influenced by the ups and downs of the value of passive pressure given water to the slopes. The most critical safety factor condition occurs during low tide conditions because there is still residual river water entering the soil pores. Analysis of stability against overturning force, shear force, and safety against bearing capacity was also declared safe.